Fostering Content-Based English Vocabulary Through Project-Based Learning in an EFL Classroom - Téllez Urrea, María Luisa Fernanda (Corporación Universitaria Minuto de Dios, 2019)
This research project was implemented in Tibabuyes Universal School. Where fifth graders lacked of vocabulary in the foreign language, to evidence that description the researcher applied a diagnostic to test both the knowledge and content related to the 3Rs (Reduce, Reuse and Recycle) and English vocabulary comprehension. Results showed that English vocabulary acquisition needed to be meaningful for the students, the researcher used PBL (Project-Based Learning) linked to the topic the use of 3Rs. Mentioned that, students were conscious about environmental care and how this assumption becomes meaningful in a foreign language acquisition. To the development of the present study, the researcher established the aim: to foster content-based English vocabulary about the 3Rs through PBL in fifth graders in an EFL classroom at Tibabuyes Universal School. The researcher implemented qualitative research paradigm taking into account instruments such as students’ artifacts, reflective field-notes and focus groups. It was evidenced the students’ process regarding vocabulary acquisition and knowledge related to 3Rs. At the end of the project, students showed the importance of wastes use in the classroom by creating products made of plastic, food and paper waste using the vocabulary gained during each session showing that English can be learn to link real life topics and English subject.
Fostering Content-Based English Vocabulary Through Project-Based Learning in an EFL Classroom
To pilot the application of project-based approach (PBL) in order to increase content-based English vocabulary acquisition and knowledge related to the 3Rs through in fifth graders in an EFL classroom at Tibabuyes Universal School.
Keywords: Reduce; Reuse and Recycle; Vocabulary Acquisition; Learning Approach; Ingles-vocabulario; Ingles (composición, ejercicios); Aprendizaje basado en proyectos